Pengaruh Struktur Modal Terhadap Kinerja Perusahaan Berdasarkan Siklus Hidup Perusahaan - Tia Ardianty Aulia; Nining Ika Wahyuni; Indah Purnamawati (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
This research aims to examine the effect of capital structure to the company's performance based on the life cycle. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2011-2015. Sampling by using purposive sampling method, that is by grouping companies into life cycle stages based on the average sales growth. The sample in this study as many as 98 companies. This research uses secondary data that the financial statements of companies manufacturing the years 2011-2015 were obtained in the Indonesia Stock Exchange. The data used include sales, debt, equity, assets and profit after tax.Methods of data analysis using Descriptive Statistics, Clasiccal Assumption Test, Regression Methods, and Hypothesis Test consisted of t Test, F Test and Coefficient of Determinatio (R Square). The results showed that the capital structure at start up, growth, and mature have a significant positive effect on company performance. The capital structure at each stage of the company life cycle is different, the greater the capital structure then the company's performance is increasing. Keywords: Capital Structure, Company Performance, Company Life Cycle, manufactur